2021
DOI: 10.3390/atmos12020240
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Boundary Layer Erosion Analysis in the Amazon Using Large-Eddy Simulation during GoAmazon Project 2014/5

Abstract: This study investigated the erosion of the nocturnal boundary layer (NBL) over the central Amazon using a high-resolution model of large-eddy simulation (LES) named PArallel Les Model (PALM) and observational data from Green Ocean Amazon (GoAmazon) project 2014/5. This data set was collected during four intense observation periods (IOPs) in the dry and rainy seasons in the years 2014 (considered a typical year) and 2015, during which an El Niño–Southern Oscillation (ENSO) event predominated and provoked an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In addition, the times when precipitation occurred were also identified in the daily visual profiles, and then the zi data during these events were disregarded. After identifying the zi values, we removed outlier values that were outside a range considered appropriate for the Amazon region (i.e., heights higher than 2.5 km during daytime) [30]. It is worth stating that the NBL heights can be overestimated, as the instrument can mistake the residual layer for the top of the ABL [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the times when precipitation occurred were also identified in the daily visual profiles, and then the zi data during these events were disregarded. After identifying the zi values, we removed outlier values that were outside a range considered appropriate for the Amazon region (i.e., heights higher than 2.5 km during daytime) [30]. It is worth stating that the NBL heights can be overestimated, as the instrument can mistake the residual layer for the top of the ABL [14].…”
Section: Methodsmentioning
confidence: 99%
“…This calculation was performed with the data collected between 08:00 and 10:00 LT. This interval was selected because it is observed that there is an approximately linear growth during this ABL phase (see Figure 3), after the NBL is completely eroded [30]. In the next step, we performed a visual inspection of all the daily cycles of the ABL height.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of modeling, previous studies [30,31] identified that the choice of PBL schemes is significant for PBLH simulation, especially at nighttime. Moreover, the appropriate depiction of nocturnal stable and morning transition stages is crucial to reproduce adequately the daytime PBL development [38].…”
Section: Introductionmentioning
confidence: 99%
“…It is important for improving the numerical weather forecast, climate modelling, and air pollution predictions. Unfortunately, large-eddy simulation (LES) studies of the morning transition (e.g., Beare 2008;Carneiro et al 2021) revealed no signs of the presence of wave activity. Another recent comprehensive LES study by Jiang (2021) showed that KHBs in an elevated shear layer (ESL) influence the underlying atmospheric layer enhancing turbulence due to the secondary instability, increasing its depth and weakening stratification; a possible impact appears to be dependent on both ESL and lower ABL characteristics.…”
Section: Introductionmentioning
confidence: 99%